W skali szarości – krótka historia srebrzystego ołowiu łączącego kolorowe szkła witrażowe - Pyka, Katarzyna (Narracje o Zagładzie, 2021)
Katarzyna Pyka discusses lead as a substance which for centuries has made possible stained glass glazing both in sacral and secular buildings. This article focuses on the uses of lead and compares the work of stained glass artists in the past and today. Contrary the associations of this craft with vivid multicolored compositions, Pyka has decided to keep her discussion in grayscale; her purpose has been to emphasize the importance of this silvery metal, which has enriched the history of art from the Middle Ages by making possible the beauty of stained glass compositions.